Ecopreneurship biology learning with local resources to raise high school student entrepreneurial interest - Yeni Suryaningsih; Ipin Aripin (Universitas Majalengka, 2022)
This study has a goal to implement entrepreneurship-based biology learning with an awareness of the sustainability of resources and the environment known as ecopreneurship. Ecopreneurship biology learning activities with local resources are expected to foster student entrepreneurial interest. Quasi-experimental method with purposive sampling technique was used in this study with tenth-grade students at senior high school involved as the subjects. Ecopreneurship biology learning is carried out through five stages (introduction, concept formation, concept integration, concept application, and product exhibition. The research instruments were questionnaire on entrepreneurial interest, observation of learning activities, and assessment of students' ecopreneur products. The findings show that the student entrepreneurial interest increases by 9.58% (low category), 76% of students are actively involved during the learning process, and the average score of ecopreneur-product making is 3.1 (good category)